Christ and the Quantum: Fundamentals of Theology of Science - Harris, Mark (Studia Philosophiae Christianae, 2025)
In light of recent scholarly dissatisfaction with ‘science and religion’ as the preferred nomenclature for an international research discipline, I explore the terminology of ‘theology of science’ as a way of clarifying the problems and aims. I engage with other recent proposals for theology of science, especially with their Christological interests. I suggest that theology of science explores what it means to hold Christ the Logos as fundamental to natural philosophy. In this light, I discuss the physical worldview of ‘quantum fundamentalism,’ and I examine realist quantum interpretations to see how theology of science might adjudicate between them. I conclude by addressing the question, ‘What was God thinking when he created the quantum world?’ ---------------------------------------- Zgłoszono: 18/08/2025. Zrecenzowano: 15/10/2025. Zaakceptowano do publikacji: 18/11/2025.